Divergent Effects of Endogenous and Exogenous Glucocorticoid‐Induced Leucine Zipper in Animal Models of Inflammation and Arthritis. Issue 5 (23rd April 2013) - Ngo, Devi; Beaulieu, Elaine; Gu, Ran; Leaney, Alexandra; Santos, Leilani; Fan, Huapeng; Yang, Yuanhang; Kao, Wenping; Xu, Jiake; Escriou, Virginie; Loiler, Scott; Vervoordeldonk, Margriet J.; et al.
Abstract Objective Glucocorticoid‐induced leucine zipper (GILZ) has effects on inflammatory pathways that suggest it to be a key inhibitory regulator of the immune system, and its expression is exquisitely sensitive to induction by glucocorticoids. We undertook this study to test our hypothesis that GILZ deficiency would exacerbate experimental immune‐mediated inflammation and impair the effects of glucocorticoids on inflammation and, correspondingly, that exogenous GILZ would inhibit these events. Methods GILZ−/− mice were generated using the Cre/loxP system, and responses were studied in delayed‐type hypersensitivity (DTH), antigen‐induced arthritis (AIA), K/BxN serum–transfer arthritis, and lipopolysaccharide (LPS)–induced cytokinemia. Therapeutic expression of GILZ via administration of recombinant adeno‐associated virus expressing the GILZ gene (GILZ‐rAAV) was compared to the effects of glucocorticoid in collagen‐induced arthritis (CIA). Results Increased T cell proliferation and DTH were observed in GILZ−/− mice, but neither AIA nor K/BxN serum–transfer arthritis was affected, and GILZ deficiency did not affect LPS‐induced cytokinemia. Deletion of GILZ did not impair the effects of exogenous glucocorticoids on CIA or cytokinemia. In contrast, overexpression of GILZ in joints significantly inhibited CIA, with an effect similar to that of dexamethasone. Conclusion Despite effects on T cell activation, GILZ deficiency had no effect on effector pathways of arthritis and was unexpectedly redundant with effects of glucocorticoids. These findings do not support the hypothesis that GILZ is central to the actions of glucocorticoids, but the efficacy of exogenous GILZ in CIA suggests that further evaluation of GILZ in inflammatory disease is required.